2013
DOI: 10.1242/dev.089722
|View full text |Cite
|
Sign up to set email alerts
|

The novel Rac effector RIN-1 regulates neuronal cell migration and axon pathfinding inC. elegans

Abstract: SUMMARYCell migration and axon guidance require proper regulation of the actin cytoskeleton in response to extracellular guidance cues. Rho/Rac small GTPases are essential regulators of actin remodeling. Caenorhabditis elegans CED-10 is a Rac1 homolog that is required for various cellular morphological changes and migration events and is under the control of several guidance signaling pathways. There is still considerable uncertainty regarding events following the activation of guidance receptors by extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…We first focused our analysis on known Rac GTPase interactors. RIN-1 is a VPS9 domain protein that interacts with GTP-bound CED-10 and controls neuronal guidance downstream of Slit-Robo signalling [ 44 ]. We found that RIN-1 is not required for PVQ development and that the penetrance of ced-10(rp100) PVQ defects is not affected by the rin-1(gk431) mutation ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We first focused our analysis on known Rac GTPase interactors. RIN-1 is a VPS9 domain protein that interacts with GTP-bound CED-10 and controls neuronal guidance downstream of Slit-Robo signalling [ 44 ]. We found that RIN-1 is not required for PVQ development and that the penetrance of ced-10(rp100) PVQ defects is not affected by the rin-1(gk431) mutation ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…They are shown to act redundantly in axon pathfinding and migration from Caenorhabditis elegans to mammalian neurons ( Lundquist et al 2001 ; Hakeda-Suzuki et al 2002 ; Luo 2002 ; Ng et al 2002 ; Lundquist 2003 ; Gonzalez-Billault et al 2012 ). A significant degree of conservation among species is also observed in Rac interactors ( Demarco et al 2012 ; Doi et al 2013 ; Law et al 2013 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, not all Vps9 subfamilies are ancient. RIN proteins are capable of binding Ras, and play roles in cell signaling, migration and adhesion, thereby linking Rab5‐mediated endocytosis and cell signaling . In addition to GEF activity for Rab5, RIN proteins are involved in Ras binding, as well as endocytosis of various signalling molecules at the cell surface.…”
Section: Resultsmentioning
confidence: 99%